Analisa Konsistensi Hukum Dalam Penetapan Isbat Nikah (Studi Kasus Penetapan Nomor 520/pdt.p/2019/pa.lmj): - Hadziq Hisbulloh Hadziq; Mahdil Mawahib (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
This writing is researching the extent of consistency of judges' decisions in court regarding the legal regulations that stipulate that the submission of a marriage confirmation (isbat nikah) when one party has passed away must be submitted in a contentious manner, meaning that there must be a family member of the deceased party as the opposing or respondent party, and the product of the marriage confirmation is in the form of a judgment, not a determination. However, the case of the marriage confirmation application in the Religious Court of Lumajang Regency, East Java, in case number 520/Pdt.P/2019/PA.Lmj, was granted by the Panel of Judges voluntarily, even though it should have been submitted as a contentious case. This research utilizes the normative juridical research method with a case approach, aiming to understand how legal rules or norms are applied in legal practice. The research findings indicate that the submission of marriage confirmation application number 520/Pdt.P/2019/PA.Lmj was not submitted in a contentious manner but was submitted voluntarily due to a legal issue, namely that the husband's family could not be seated as heirs because all of them are non-Muslims (Hindus) and therefore cannot be categorized as heirs.